2021
DOI: 10.1002/tax.12526
|View full text |Cite
|
Sign up to set email alerts
|

Repeated parallel losses of inflexed stamens in Moraceae: Phylogenomics and generic revision of the tribe Moreae and the reinstatement of the tribe Olmedieae (Moraceae)

Abstract: We present a densely sampled phylogenomic study of the mulberry tribe (Moreae, Moraceae), an economically important clade with a global distribution, revealing multiple losses of inflexed stamens, a character traditionally used to circumscribe Moreae. Inflexed stamens facilitate ballistic pollen release and are associated with wind pollination, and the results presented here suggest that losses of this character state may have evolved repeatedly in Moraceae. Neither Moreae nor several of its major genera (Moru… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 72 publications
(128 reference statements)
0
10
0
Order By: Relevance
“…Finally, the relationships among species within genera are also consistent with previous work (except for Muehlenbeckia , see next paragraph), some based on plastid DNA (Maurin, 2020b for Pennantia , Maurin & Smissen, 2021 for Corokia ); others on nuclear ribosomal markers (e.g. Gardner et al ., 2021 for Streblus ; Mitchell et al ., 2009 for Melicytus ; Appelhans et al ., 2014 for Melicope ) or based on morphological characters (e.g. Aagesen, 1999 for Discaria ).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the relationships among species within genera are also consistent with previous work (except for Muehlenbeckia , see next paragraph), some based on plastid DNA (Maurin, 2020b for Pennantia , Maurin & Smissen, 2021 for Corokia ); others on nuclear ribosomal markers (e.g. Gardner et al ., 2021 for Streblus ; Mitchell et al ., 2009 for Melicytus ; Appelhans et al ., 2014 for Melicope ) or based on morphological characters (e.g. Aagesen, 1999 for Discaria ).…”
Section: Resultsmentioning
confidence: 99%
“…It is clear that the genus Morus is monophyletic and is divided into five clades ( Figure 4 ). Recently, M. mesozygia and M. insignis , native to Africa, which used to belong to the Morus genus, were eliminated from the Morus genus on the basis of phylogenetic analyses of supercontig sequences from 246 Moraceae samples ( Gardner et al., 2021 ). Here, we also found that M. mesozygia did not belong to Morus because M. mesozygia was clustered with Ficus and Broussonetia ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…In 14 different groups, each group randomly selected a representative CP genome, together with other 36 CP genomes from the unclassified group, to form 50 CP genomes for phylogenetic analysis. The CP genome sequences of Broussonetia papyrifera ( Broussonetia genus, GenBank: MZ662865), Ficus carica ( Ficus genus, GenBank: KY635880) and Morus mesozygia ( Afromorus genus, GenBank: MZ274134) ( Gardner et al., 2021 ) were selected as outgroups. All complete CP genome sequences were aligned using MAFFT v7.455 ( Katoh and Standley, 2013 ), and the alignments were trimmed with trimAl v1.4.rev15 ( Capella-Gutiérrez et al., 2009 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations